PERAN KEPROFITAN DALAM MEMEDIASI PENGARUH LEVERAGE TERHADAP NILAI PERUSAHAAN: BUKTI DARI INDUSTRI PERBANKAN INDONESIA - Nurul Fitriyani Pratiwi; Ario Purdianto; Agustina Agustina (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study seeks to analyze the correlation between leverage and company value with profitability serving as an intermediary mechanism in banking companies listed on the Indonesia Stock Exchange over the observation period of 2022–2024. This research employed a quantitative methodology, utilizing path analysis and mediation assessment using the Sobel test. The study sample included 26 conventional commercial banks selected based on specific criteria through purposive sampling. Empirical findings in this study indicate that company value is not directly influenced by leverage, while an increase in leverage is statistically proven to decrease a company's profitability. Furthermore, profitability levels were discovered to have a significant and beneficial relationship with company value, while also serving as an intermediary variable that facilitates the impact of leverage on company value. These results verify that the influence of leverage on company value is indirect, as it operates through profitability, which serves as a channeling mechanism in this relationship.